Preserving the functional asymmetry of the muscular system in young hockey players through compensatory exercises - Mironov, A. O.; Spiridonov, E. A.; Khutin, S. A.; Ponimasov, O. E. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assessment of the interplay between the integration of remedial exercises into training and the outcomes of specific assessments for young hockey players. Methods and structure of the study. The participants in the research were young hockey players aged between 13 and 14. The hockey players underwent a series of training and evaluation throughout the course of a single season. The players engaged in a 45-minute twice-weekly training regimen that included exercises designed to strengthen the core muscles, enhance flexibility, and improve joint mobility. Results and conclusions. Corrective exercises can mitigate the adverse consequences of unilateral exercises and decrease the likelihood of overexertion for the athlete. The process of corrective exercises is based on the comprehensive improvement of joint flexibility and mobility, as well as the ability to move in different directions while skating and using a stick and puck.